Digital Accounting Transformation to Enhance Efficiency, Accuracy, and Competitiveness in the Modern Era - Sari Rahayu; Masyhuri Masyhuri (Journal of Management, Entrepreneurship, and Tourism, 2026)
Digital transformation has fundamentally reshaped the role of accounting within modern organizations, positioning accounting systems as strategic instruments that support operational performance, information quality, and competitive sustainability. This study aims to analyze the role of digital accounting transformation in enhancing operational efficiency, financial information accuracy, and corporate competitiveness in the contemporary business environment. The research employs a non-empirical qualitative design based on a systematic literature review approach. Relevant literature was collected from scholarly databases and analyzed using an integrative thematic synthesis framework to identify recurring patterns, conceptual relationships, and emerging trends. The findings indicate that digital accounting technologies, including cloud-based systems, integrated accounting information systems, financial technologies, and automated reporting mechanisms, significantly improve operational efficiency through process optimization and reduced administrative complexity. The analysis further reveals that digitalization enhances the accuracy, consistency, transparency, and reliability of financial information by strengthening data validation and reporting controls. Competitive advantage emerges through improved decision-making quality, organizational adaptability, innovation capability, and responsiveness to market dynamics. The study concludes that digital accounting transformation functions as a strategic organizational capability that generates sustainable value when technological integration is aligned with managerial objectives and long-term business strategy.